Modal analysis of an 8/6 pole switched reluctance motor core with different materials and assembly method using FEA - Rosli, Danial N.; Rasid, Mohd Azri Hizami (Penerbit UMP, 2022)
Vibration causes acoustic nuisance, aggravating fatigue etc. Knowing that resonance is caused by amplified deformation when a structure is excited at natural frequency, modal analysis is important to identify the natural frequency and mode of deformation that may be excited in electrical machine. This study analyzes the natural frequency and mode shape of major components in 120v 4-Phase 8/6 Pole Switched Reluctance Motor. The material selected are materials that are commonly employed for electrical machines components. It was found that gray cast iron core has the lowest natural frequency for each mode from 1 to 3. This is mainly due to its lower elasticity modulus (10 times smaller in comparison to other materials). Solid and slinky rotor has a very low first mode natural frequency at tens of Hz, which is very susceptible to mechanically induced excitation vibration.